Pengukuran Kinerja Gudang Dengan Menggunakan Metode Balanced Scorecard – Studi Kasus Pada PT. GMS - Jakarta - Agung Chandra (Jurnal METRIS, 2014)
Market competition in food industry is growing tougher and tougher. More accurate quality service and faster delivery time are customer demands. One way to achieve them is to improve logistics and warehouse sector. Performance measurement must be established and monitored periodically. The research is conducted by using Balanced Scorecard at PT. GMS – Jakarta. The result has shown that three aspects: financial, customer, internal process must be maintained and one aspect must be improved: learning and growth